Anticoagulants - The Past, The Present, The Future - A Systematic Review - Warzycka, Klaudia; Maliszewska, Karolina; Woźniak, Kinga; Gardian-Baj, Monika; Jung, Magdalena; Hedesz, Patryk; Jung, Maximilian; Doryń, Aleksandra; Jędral, Krystian; Włodarczyk, Aleksandra; Szczerbiak , Alicja (Journal of Education, Health and Sport, 2024)
Introduction: Anticoagulants have been discovered and developed over past 100 years. At the beginning unfractionated heparin found its applications, just later to fade into the background of newer and more effective drugs. Patients have been treated with more progressive medications – Low-Molecule-Weight Heparin (LMWH), Vitamin K Antagonists (VKA) and Novel Oral Anticoagulants (NOAC). As for today, deemed a turning point in anticoagulant therapy are inhibitors of factor XI. It is a ground-breaking innovation as it ensures high prevention of thrombotic episodes and guarantees intact physiological hemostasis.Current State of Knowledge: The coagulation cascade and molecules part taking in that have been discovered and described extensively and in detail. Unfractionated heparin is the oldest out of all and despite its simple action mechanism and adverse effects, is still a requested drug. Its lighter form, low-molecule-weight-heparin (LMWH) is an enhancement to the previous treatment due to its higher bioavailability and fewer side effects. Vitamin K antagonists (VKAs) are widely spread in medical environment thanks to their expanded mechanism of action, oral administration and reversibility of their overdose, as well as their well-developed anti-side effect therapy. Novel Oral Anticoagulants (NOACs) have been introduced to the market about 10 years ago. In spite of NOACs short period of clinical use, they were a huge change to the previous treating methods. Currently, the newest innovation in anticoagulant therapy are inhibitors of factor XI and its clinical trials outcome is promising for the future.Summary: The present article discusses history of anticoagulant drugs, their mechanism of action and usage but also focuses on the recent perspectives and developments as new anticoagulant drugs are being put to the test in therapeutic trials. The review underlines the importance of improvements in old therapeutic methods and exploring the new, more suitable ones.